13. Biology of Sargassum crassifolium J. Agardh from Lucolan Shoal, Panguil Bay (Mindanao, Philippines): I. Growth Rate - Barquilla, Manuel; Rosales-Apao, Patricia (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
The growth rate of cut and uncut thalli of Sargassum crassifolim J. Agardh under natural conditions in Lucolan Shoal, Panguil Bay was studied within a thirteen - month period. Uncut thalli served as the control while some thalli had the stipe cut 1 cm from the holdfast or the lateral cut 1 cm from the stipe of the main branch. Growth rate refers to the length increase in the stipe or the regenerating laterals. The growth rate of regenerating offshoots and stipe from the three experimental set-ups varied showing a seasonal pattern. Longer laterals or regenerating offshoots were longer during the onset of reproductive phase of Sargassum crassifolium. The cutting of the stipe increased the daily growth rate (DGR) while cutting the laterals increased the numbers of emerging or regenerating offshoots. It is recommended that Sargassum crassifolium be cut or harvested with trimmers during the start of the reproductive phase when much biomass is expected.